VideoHQescultura: uma poética narrativa - Machado, Fábio Purper (2017)
These are the processes of an artist researcher who discusses his poetic and traces its dialogues with operational concepts from different origins. The artistic work that is covered here consists of a series of creations of my own, which I call videocomicsculptures, and are defined as narratives in movement between the artistic fields of sculpture, comics and video. I choose to focus this research on the ones that result in videos, and that come to be permeated by issues from the fields of film, photography and animation. Relations between the senses of touch and vision that are experienced with the videocomicsculptures dialogue with the “Tactile Vision Theory” (José Val Del Omar) and with the concept of “image-time” (Gilles Deleuze), which contributes to this work with the notion of a cinema that proposes blocks of sensation with the materiality of filmed objects. There is a dialog with the “sculpture effect” (Régis Durand, Phillipe Dubois), by valuing tridimensionalities in the flat support of the video, and with the notions of “transmedia narrative” (Henry Jenkins, Edgar Franco) and “expanded comics” (Gazy Andraus), among other concepts that involve the plurality of means of telling stories. Relations between image and writing that are present in the videocomicsculptures are also addressed, as well as issues in common with poetics of other artists within these areas and especially in movement between them. Moreover, the tergiversative feature present in the textual portion of several of the works that compose the body of this research is taken as the guiding thread for the establishment of a fictional universe, here baptized “Fictional Tergiverse”. Some parameters and benchmarks are then developed for an initial exploration of an artistic field that is made of movements and boundary works between these chosen artistic fields.